The Guardian test - Soontornvat, Christina; Hong, Kevin, Illustrator (New York : Scholastic Press, 2023)
Young Plum is shocked to discover that she's been accepted to the Guardian Academy on Lotus Island, an elite school where kids learn how to transform into Guardians, magical creatures who are sworn to protect the natural world. The Guardian masters teach Plum and her friends how to communicate with animals and how to use meditation to strengthen their minds and bodies. All the kids also learn to fight, so they can protect the defenseless if needed. To her dismay, Plum struggles at school. While her classmates begin to transform into amazing creatures, Plum can't even seem to magic up a single feather! If she can't embrace her inner animal form soon, she'll have to leave school and lose the first group of real friends she's ever known.
Publishers Weekly, January 2023
3.5
3-6
Keywords: Shapeshifting -- Juvenile fiction; Friendship -- Juvenile fiction; Magic -- Juvenile fiction; Human-animal communication -- Juvenile fiction; Schools -- Juvenile fiction; Shapeshifting -- Fiction; Friendship -- Fiction; Magic -- Fiction; Human-animal communication -- Fiction; Schools -- Fiction; Fantasy fiction; School fiction